A combinatorial guide to phase formation and surface passivation of tungsten titanium oxide prepared by thermal oxidation. (March 2020) - Siol, Sebastian; Ott, Noémie; Beall, Casey; Stiefel, Michael; Unutulmazsoy, Yeliz; Döbeli, Max; Tilley, S. David; Schmutz, Patrik; Jeurgens, Lars P.H.; Cancellieri, Claudia
Abstract: TiO2 and WO3 are two of the most important earth-abundant electronic materials with applications in countless industries. Recently alloys of WO3 and TiO2 have been investigated leading to improvements of key performance indicators for a variety of applications ranging from photo-electrochemical water splitting to electrochromic smart windows. These positive reports and the complexity of the ternary W-Ti-O phase diagram motivate a comprehensive experimental screening of this phase space. Using combinatorial thermal oxidation of solid solution W1- x Ti x precursors combined with bulk and surface analysis mapping we investigate the oxide phase formation and surface passivation of tungsten titanium oxide in the entire compositional range from pure WO3 to TiO2 . The system shows a remarkable structural transition from monoclinic over cubic to tetragonal symmetry with increasing Ti concentration. In addition, a strong Ti surface enrichment is observed for precursor Ti-concentrations in excess of 55 at.%, resulting in the formation of a protective rutile-structured TiO2 surface layer. Despite the structural transitions, the optical properties of the oxide alloys remain largely unaltered demonstrating an independent control of multiple functional properties in W1- x Ti x O n . The results from this study provide valuable guidelines for future development of W1- x Ti x O n for electronic and energy applications, but also novel engineering approaches for surface functionalization and additive manufacturing of Ti-based alloys. Graphical abstract: Using combinatorial thermal oxidation of solid solution W1- x Ti x precursors combined with bulk and surface analysis mapping we investigate the oxide phase formation and surface passivation of tungsten titanium oxide in the entire compositional range from pure WO3 to TiO2 . Image, graphical abstract